1985
DOI: 10.1002/jcp.1041250333
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin receptor regulation is coupled to intracellular ferritin in proliferating and differentiating HL60 leukemia cells

Abstract: Cultured myeloid leukemia cells display transferrin receptors but decrease receptor display after differentiation induction or accumulation of intracellular iron. To determine whether regulation of transferrin receptors and ferritin were linked under these disparate conditions, serum-free and fetal bovine serum (FBS) cultures of HL60 promyelocytic leukemia cells were used to investigate relationships between transferrin receptor display and intracellular ferritin. Using 125I-transferrin binding and immunofluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…This estimation is similar to previously reported subunit molecular weights of transferrin receptors isolated from other cell types (Hamilton et al 1979, Seligman et al 1979, Omary et al 1980, Enns & Sussman 1981, Haynes et al 1981, Sutherland et al 1981, Bleil & Bretscher 1982, Schneider et al 1982, Fuller & Simons 1986. The affinity of receptors present on intact cells and in detergent-solubilized U937 cell extracts was in the nM range, also consistent with previously reported results (Hamilton et al 1979, May et al 1984, Musgrove et al 1984, Taetle et al 1985, Fuller & Simons 1986, Nishimura et al 1986). In addition, we demonstrated a large pool of intracellular transferrin U937 transferrin binding sites.…”
Section: Discussionsupporting
confidence: 90%
“…This estimation is similar to previously reported subunit molecular weights of transferrin receptors isolated from other cell types (Hamilton et al 1979, Seligman et al 1979, Omary et al 1980, Enns & Sussman 1981, Haynes et al 1981, Sutherland et al 1981, Bleil & Bretscher 1982, Schneider et al 1982, Fuller & Simons 1986. The affinity of receptors present on intact cells and in detergent-solubilized U937 cell extracts was in the nM range, also consistent with previously reported results (Hamilton et al 1979, May et al 1984, Musgrove et al 1984, Taetle et al 1985, Fuller & Simons 1986, Nishimura et al 1986). In addition, we demonstrated a large pool of intracellular transferrin U937 transferrin binding sites.…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with immunohistochemical data on testicular Tf binding sites (Brown, 1985). However, the cellular uptake of Tf-bound iron by different cell types can be influenced in a complex manner by marked effects of Tf and iron on the number of Tf receptors and the ferritin content (Rhyner et al, 1985;Rao et al, 1986). Such effects may result in altered kinetics of iron uptake by isolated and cultured cells.…”
Section: Discussionsupporting
confidence: 89%
“…Tf receptors are mainly present on immature, undifferentiated cells and the number of receptors decline when cells differentiate (Rhyner et al, 1985;Petraki et al, 1986). In this context, spermatogenic cells may be considered as immature cells.…”
Section: Discussionmentioning
confidence: 99%
“…The factor regulating the number of transferrin receptors must be determined. Cellular ferritin seems to be an important regulator of myeloid differentiation [19] [20] in HL60 cells, a promyelocytic leukemia cell line. Ward et al [21] showed that intracellular heme, rather than ferritin, modulates the number of transferrin receptors on Hela cells.…”
Section: Discussionmentioning
confidence: 99%